Rainfall Erosivity in Soil Erosion Processes - Diodato, Nazzareno (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book gathers recent international research on the association between aggressive rainfall and soil loss and landscape degradation. Different contributions explore these complex relationships and highlight the importance of the spatial patterns of precipitation intensity on land flow under erosive storms, with the support of observational and modelling data. This is a large and multifaceted area of research of growing importance that outlines the challenge of protecting land from natural hazards. The increase in the number of high temporal resolution rainfall records together with the development of new modelling capabilities has opened up new opportunities for the use of large-scale planning and risk prevention methods. These new perspectives should no longer be considered as an independent research topic, but should, above all, support comprehensive land use planning, which is at the core of environmental decision-making and operations. Textbooks such as this one demonstrate the significance of how hydrological science can enable tangible progress in understanding the complexity of water management and its current and future challenges.